The seleclion ai genetic materiaIs in piant breeding pragrams. i. The discriminative power of lhe ranking. - Zimmermann, Francisco José P.; Conagin, Armando (Pesquisa Agropecuaria Brasileira, 2013)
In some phase ol lhe piant improvement process, a large number of materiais must be nvaluated tor the selection 01 the best ones. In this case lhe experimental designs more frequently used in breeding programs are the square laltice designs, and only the best treah -nenls based on lhe yield or another criterion are selected according to some selection criterion. Trying lo gel intormations about the ettect on the discriminalive power 01 number of replications, coefficient 01 varialion and discrepancy ol lhe boabnents in relation tolhe mean, 1400 experimenta in a 5 x 5 square laffice design were simulated, with treatrnent eflects ranging between + 25% and - 25% of lhe mean. It was verilied that lhe ranking discriminatory power ol lhe eahnents are increased as the coefftcient of varialion gets lower and the number ot replicalions increases. For the case o? 12 replications and C.V. = 15% a discilminative power larger lhan 75% was observed when the ditierence between the selecled material and the mean was 0125% 0f magnitude, and was less than 50% when lhese differences were siluated between 10% and 7%.